2007
DOI: 10.1038/nature06419
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the sodium–potassium pump

Abstract: The Na+,K+-ATPase generates electrochemical gradients for sodium and potassium that are vital to animal cells, exchanging three sodium ions for two potassium ions across the plasma membrane during each cycle of ATP hydrolysis. Here we present the X-ray crystal structure at 3.5 A resolution of the pig renal Na+,K+-ATPase with two rubidium ions bound (as potassium congeners) in an occluded state in the transmembrane part of the alpha-subunit. Several of the residues forming the cavity for rubidium/potassium occl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
756
1
38

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 821 publications
(841 citation statements)
references
References 52 publications
32
756
1
38
Order By: Relevance
“…To reveal the observed difference in Na + ,K + -ATPase inhibition at molecular level, the examined steroid-like compounds were subjected to molecular modeling and docking, as exemplified by bufalin and ursolic acid, to the extracellular domain of Na + ,K + -ATPase α subunit. As expected from structural similarity, the interaction of bufalin with the binding pocket of Na + ,K + -ATPase nearly matched to that of ouabain reported previously [7] with the unique lactone ring (indicated by a pink arrow) penetrating deeply into the cavity close to two K + binding sites ( Figure 4A). Comparably, the hydrophobic steroidal core of ursolic acid was confined in a location similar to that of bufalin within the binding pocket of Na + ,K + -ATPase ( Figure 4B).…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…To reveal the observed difference in Na + ,K + -ATPase inhibition at molecular level, the examined steroid-like compounds were subjected to molecular modeling and docking, as exemplified by bufalin and ursolic acid, to the extracellular domain of Na + ,K + -ATPase α subunit. As expected from structural similarity, the interaction of bufalin with the binding pocket of Na + ,K + -ATPase nearly matched to that of ouabain reported previously [7] with the unique lactone ring (indicated by a pink arrow) penetrating deeply into the cavity close to two K + binding sites ( Figure 4A). Comparably, the hydrophobic steroidal core of ursolic acid was confined in a location similar to that of bufalin within the binding pocket of Na + ,K + -ATPase ( Figure 4B).…”
Section: Resultssupporting
confidence: 54%
“…The crystal structures of pig renal Na + ,K + -ATPase (PDB code 3B8E) and shark rectal gland Na + ,K + -ATPase (PDB code 3A3Y) were downloaded from Protein Data Bank and found to posses equivalent structures [7,8] . In order to facilitate docking process, the β and γ subunits of the Na + ,K + -ATPase were removed, as well as the water molecules and counter-ions surrounding the remaining α subunit.…”
Section: Molecular Modeling and Dockingmentioning
confidence: 99%
“…Na, K-ATPase consists of α and β subunits. The glycosylated β subunit has been proposed to facilitate the assembly and transport of the α subunit from the endoplasmic reticulum to the plasma membrane (20,21), and the β subunit is the key factor in polarizing distribution of Na, K-ATPase (22). The results of the present study showed that the HCMV UL136 protein has the ability to interact with ATP1B1.…”
Section: Discussionsupporting
confidence: 54%
“…Crystal structures of pig and shark Na,K-ATPase in both the absence [3,4] and presence of ouabain [5,6] have been determined. There is a strong similarity between the structures of the shark and pig a-subunits, and ouabain-induced re-arrangements can be seen for the enzymes from both species.…”
Section: Introductionmentioning
confidence: 99%